Refugees, Evacuees, and Repatriates: Biafran Children, UNHCR, and the Politics of International Humanitarianism in the Nigerian Civil War. (September 2020) - Ibhawoh, Bonny
Abstract: The Nigeria-Biafra war contributed to the rise of post-colonial moral interventionism, ushering in a new form of human rights politics. During the war, relief agencies evacuated 4, 000 children from the conflict zones to Gabon and Côte d'Ivoire to protect them from the conflict. This was part of a broader international humanitarian airlift operation that brought relief supplies to the besieged Biafra territory. At the end of the war, most of the children were returned to their homes in Nigeria through an international humanitarian repatriation effort. Ibhawoh examines how state interests and the politics of international humanitarian interventionism manifested in debates about classifying and protecting displaced children, the most vulnerable victims of the conflict.